EKSISTENSI PENCIPTA LAGU DAN/ATAU MUSIK SETELAH PERATURAN PEMERINTAH NOMOR 56 TAHUN 2021 DISAHKAN - Sri Wahyuni Muhtar; Faisal Faisal (Universitas Negeri Surabaya, 2021)
Based on the phenomenon of the endorsement of PP Number 56 of 2021, formulated research questions, namely how the songwriter responds after the rule is passed, and what impact the rule has on the existence of the songwriter. This research aims to find out the response and impact of PP No.56 of 2021 for songwriters, as well as help the government in the socialization of the rules. The research method used is qualitative with data reduction procedures, data classification, data presentation, conclusion withdrawal and verification of data from data collection results through interviews, participant observations and documentation. The results showed that the positive response of songwriters after PP Number 56 of 2021 was passed through self-registration and work in LMK creator rights, as well as registering works online at DJKI Kemenkumham. But there are also songwriters who have not responded to registering works institutionally because of concerns that creation will be consumed on a limited basis so as to provide publication losses for creators. Furthermore, the impact of these rules on the existence of songwriters is to make creators more productive to produce works periodically, the creation of works becomes more quality and quality in the world of the music industry, and the right to publish songwriters exist in the community and exist on the side that utilizes national and international works.